A new genus of Scolebythidae (Hymenoptera: Chrysidoidea) from the Early Cretaceous of China - Cai, Yaping; Zhao, Yunyun; Shih, Chungkun; Ren, Dong (Zootaxa, 2012)
A new genus Mirabythus Cai, Shih et Ren, gen. nov. (type species, M. lechrius Cai, Shih et Ren, sp. nov.) and M. liae Cai, Shih et Ren, sp. nov. from the family Scolebythidae are described from the Early Cretaceous Yixian Formation of Huangbanjigou Village, Liaoning Province, northeastern China. These findings extend the existence of Scolebythidae to the Early Cretaceous of China, while providing evidence to support Engel and Grimaldi’s hypothesis that the family was widely distributed throughout the Cretaceous. Our two new species with clear venation also provide a comprehensive understanding of the venational changes from the Early Cretaceous to now. A key to the fossil and extant genera of Scolebythidae is provided.